NEW TECHNOLOGIES IN PARK DESIGN - M.R. Borodina (American Journals Publishing, 2023)
The modern amusement park is a unique, high-tech complex of cultural, recreational, sports, health and recreational facilities, allowing human experience, thanks to the use of VR technology.
Keywords: project, innovation, park, immersion, virtual reality, archaeology, city, 3D modelling, virtual reality park.